Tu jie guo shu zai pei yu zheng xing xiu jian ru men - Wang, Danxia; Nippon Beauty Society (Beijing : China Machine Press, 2022)
This book selects 11 representative fruit tree varieties and explains the professional skills of cultivation and plastic pruning of these fruit trees in an easy-to-understand way, such as colonization, plastic pruning, artificial pollination, flower thinning, fruit thinning, harvesting and other basic operations, and through a large number of photos and diagrams, readers can see at a glance and quickly master the skills, even those who cultivate fruit trees for the first time can successfully harvest delicious fruits.
Keywords: Fruit -- Culture; Fruit gardening